Mechanism for assessing the adaptive reserves of elite wrestlers under anaerobic energy supply conditions - Chernozub, A.; Korobeynikov, G.; Zoriy, Y.; Koval, V.; Husieva, I.; Hryhoriev, V.; Xianyu, W.; Khasanov, O.; Potop, V. (Journal of Physical Education and Sport, 2024)
Background and study aim: Development an effective system for evaluating and enhancing the adaptive reserves of elite wrestlers is critical issue in professional sports. The challenge of optimizing the functional training of athletes with high resistance to physical loads is particularly pressing. The purpose of this study is to create a mechanism for assessing the adaptive body reserves of elite wrestlers under anaerobic energy supply conditions.